Knowledge, attitude, and practice toward COVID-19 transmission, prevention, and self-quarantine management among public servants in selected locations of the Sidama region, Southern Ethiopia: a multicenter cross-sectional study - Borie, Yacob Abraham; Yeheyis, Tomas; Deribe, Bedilu; Ayalew, Mohammed; Reta, Yared; Hoyiso, Dawit; Jembere, Wegene (Frontiers in Public Health, 2023)
Background: The COVID-19 epidemic is putting an enormous strain on the world's healthcare systems, lifestyles, and quality of life. Ethiopia attempted to meet the myriad needs of its people as the COVD-19 epidemic was approaching and in order to lessen the epidemic's impact on the populace, the government was demonstrating a strong commitment. Despite this fact, the population's compliance with measures was not as needed. Objectives: To assess knowledge, attitude, and practice regarding covid-19 transmission, prevention, and self-quarantine management among public employees in selected towns of Sidama region, Southern Ethiopia, 2020. Methods: Institution-based cross-sectional study was conducted from October 01 to 30, 2020 among 399 public servants in selected towns of Sidama region, Sothern Ethiopia. A one-stage cluster sampling was used to randomly select 16 public service sector offices from the total 32 sector offices in the selected towns of the region. Simple random sampling was employed to select respondents following equal distribution of the samples to 16 sector offices. Data were collected by using an adapted self-administered questionnaire. Data entered using epi-data version 3.1 and SPSS version 24 was used for statistical analysis. Descriptive statistics used to compute frequency, percentage, and mean for independent and dependent variables Result: Overall, 42.36% of respondents had good knowledge of COVID-19, while the remaining 57.64percent had poor knowledge. Attitude toward COVID-19 prevention and control was 65.2% favorable, 54.4% of respondents had a good level of practice of COVID-19 preventive and control measures and 52.4% of the respondents had a good level of knowledge on self-quarantine management. Conclusion: The level of knowledge, attitude, practice, and self-quarantine management in the area is insufficient for preventing and controlling the disease. Evidence-based awareness creation and law enforcement in the study areas and surroundings, with an emphasis on infection prevention and control (IPC) in the public sector and other public gathering areas is recommended.